소방공무원의 개인, 직무 및 건강관리 특성이 근골격계질환과 직무스트레스에 미치는 영향 조사 - 하강훈; Kang Hun Ha; 소수현; Soo-hyun So; 이경선; Kyung-sun Lee (한국안전학회지, 2017)
The purpose of this study is to analyze the effects of personal, job, and health care characteristics of firefighters on musculoskeletal disorders (MSDs) and job stress. This survey was participated 591 firefighters in jeonnam and Busan city. The survey consisted of 1) personal, job, and health care characteristics measurement, 2) job stress measurement (KOSS, Korean Occupational Stress Scale), 3) musculoskeletal disorders symptoms mesurement. The analysis of the data was using SAS 9.1 Ver. The statistics analysis was performed the frequency, percentage, average, and standard deviation for each survey item. The Chi square analysis was performed to analyzed the effects of personal, job, and health care characteristics on MSDs and job stress. According to the results of the study on musculoskeletal disorders symptoms, 49.6% of the subjects perceived pain related to musculoskeletal diseases. The total score for job stress was 51.6 (SD 12.9), which was the highest 50% when compared to the Korean job stress standard (male). Age, department, work experience, working type, position, and sleeping time were found to affect musculoskeletal disorders and job stress.